A Multiscale Morphological Insight into Graphene Based Coatings for Pool Boiling Applications. Issue 15 (14th September 2018) - Gupta, Anju; Jaikumar, Arvind; Kandlikar, Satish G.; Rishi, Aniket; Layman, Andrew
ABSTRACT: The application of graphene for pool boiling is an attractive option to facilitate compaction and promote efficient heat removal from high power density devices. In this context, chemical characterization of the depositions achieved through commonly employed coating techniques are an important topic of discussion. A detailed structure-property relationship between the morphologies obtained on the mono and multilayered graphene coatings and their corresponding pool boiling performance quantified by the experimental critical heat fluxes is presented. Three different types of graphene (G) and graphene oxide (GO) substrates are characterized: (i) nanoscale: mono and multilayer samples developed through chemical vapor deposition, (ii) Rochester Institute of Technology (RIT)-G/GO colloid generated through an oxygen embrittlement electrochemical process, and (iii) commercially available chemical vapor deposited (CVD)-G/GO colloid. The morphological features were characterized with scanning electron microscope while X-Ray Diffractometer analysis and Raman spectroscopy were used to examine the ordering and stacking of the sheets that result in the unique structural features. Fourier transform infrared and energy dispersive X-ray spectroscopy were employed to identify the overall compositional characteristics of the coated surfaces. The wettability changes and additional nucleation sites for nanoscale coatings, and multiscale roughness features and ridge microstructures for microscale coatings were identified as enhancement mechanisms.